Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Narcissism, femininity and alienation - Bartky, Sandra Lee (Social Theory and Practice, 1982)
https://www.jstor.org/stable/23559009#metadata_info_tab_contents
Keywords: amériques; cours; discipline; fem1000; féminisme marxiste; philosophie politique; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques; états-unis

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

Nous nous définissons comme esclaves des esclaves - Front de libération des femmes du Québec (Québécoises deboutte!, 1982)
Donné en lecture cours FEM1000: p.65-67
Keywords: 1900-1999; amériques; cours; fem1000; histoire des femmes*; histoire et politique; militance; mouvements sociaux; nationalisme; premier cycle; périodes historiques; québec; régions géographiques; thématiques

The daughter's seduction: Feminism and psychoanalysis - Gallop, Jane (Cornell University Press, 1982)
At the time this book was published in 1982, Jane Gallop was professor of French at Miami University; she has also written Intersections: A Reading of Sade with Bataille, Blanchot, and Klossowski. She wrote in the Introduction, "[the book] studies the relation between contemporary feminist theory and the psychoanalysis of Jacques Lacan... it enters into a network of problems: problems of sexual difference, of desire, of reading, or writing, of power, of family, of phallocentrism and of language... this book is ... a contribution to the sort of thinking it describes—that is, a contribution to French psychoanalytic feminist thought from the vantage point of these English-speaking shores." (p.11) She adds, "The book begins by calling into question certain feminist assumptions through the agency of Lacanian psychoanalysis. It ends by calling into question certain psychoanalytic positions through the agency of feminist writing." (p.15) She states that "[Freudian] Phallocentrism seems wrong to [Ernest] Jones: that is, immoral by virtue of being 'excessive, immoderate,' which is to say, unreconcilable with a 'sense of proportion.' The phallic disproportion brings him... to champion the claims of an 'underestimated' female sexuality to a more balanced, more proportionate estimate. His 'sense of proportion,' his spirit of fair play, will be sufficiently scandalized to provoke his only major departure from Freud's theory." (p. 16) She observes that in an article, "[Stephen] Heath begins by informing us that ... Lacan's 1972/73 seminar [is] devoted to 'what Freud expressly left aside... What does woman want?' ... Yet Lacan said nothing of devotion... Lacan speaks of a beginning... of a relation to this question: far from devoting himself to women he is simply at the stage of approach, first and rather aggressive encounter." (p. 43) This book will be of interest to feminists studying psychoanalysis, or to students of Lacan.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; thématiques; écriture des femmes*; états-unis

Québécoises deboutte! - O'Leary, Véronique; Toupin, Louise (Les éditions du remue-ménage, 1982)
Québécoises Deboutte! c’est non seulement l’accession à l’écriture de ce féminisme québécois organisé sur la base d’un groupe autonome de militantes, mais c’est aussi la première revue d’analyse théorique de l’exploitation des femmes, avec ses recherches, ses tâtonnements et ses acquis importants.
Keywords: 1900-1999; amériques; anthologie; cours; fem1000; histoire et politique; militance; mouvements sociaux; mémoire collective; premier cycle; périodes historiques; québec; régions géographiques; thématiques